Hush [compact disc, unabridged] - Patterson, James, 1947-; Fox, Candice (Patterson, James, 1947- Detective Harriet Blue, 2020)
Prison is a dangerous place for a former cop, as Harriet Blue is learning on a daily basis. The last person she wants to see is Deputy Police Commissioner Joe Woods, but he's ready to offer her a deal.